IMPLEMENTASI STRATEGI DENGAN MENGGUNAKAN BALANCED SCORECARD DALAM MENGUKUR KINERJA MANAJEMEN - Agustina, Liony; Retnani, Endang Dwi (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
The purpose of this research is to find out and to analyze the strategy implementaion which is done by using balanced scorecard in order to measure the management performance of a company so it is conformed to the vision and mission which is desired to be achieved. The research object is PT PELNI (Persero) Surabaya branch. The method has been done by using qualitative method. The result of the analysis shows that balanced scorecard is the method which interprets the vision, the mission and the strategy into strategy targets of performance measure in four perspectives i.e.: the financial perspective is measured by ROI, profit growth rate, and income growth rate shows unfavorable results due to the decrease in income; the customer perspective is measured by the customer acquisition, customer retention, and customer satisfaction survey which show quite well resut; the internal business process perspective is measured by new facilities and services which are provided after the transaction show the capacity of the company as a good company; and the growth and learning perspective is measured by employee retention, employee satisfaction surve, and employee training show a good result. It can be concluded from the result of the analysis that balanced scorecard can be used as strategy implementation instrument in measuring the management performance by using financial and non-financial perspective.Keywords: implementation strategy, balanced scorecard, management of performance measurement.